In situ diagnosis of Li-wall conditioning and H/D co-deposition on the first wall of EAST using laser-induced breakdown spectroscopy. (11th July 2018) - Liu, P; Zhao, D Y; Sun, L Y; Fu, C L; Liu, J M; Li, C; Hai, R; Sang, C F; Hu, Z H; Sun, Z; Hu, J S; Wang, L; et al.
Abstract: In this work, laser-induced breakdown spectroscopy (LIBS) approach was applied to Experimental Advanced Superconducting Tokamak (EAST) device for in situ diagnosing the lithium-wall conditioning processes and the Li-H/D co-deposition on the inner board of the first wall of EAST. The fuel of D and the co-deposition impurities, such as H, Li, Ca, Na and Mo were clearly observed on the surface of the first wall. During the processes of Li-wall conditioning, the Li signal intensity increases with the increase of the time of Li-wall conditioning, and the average deposited rate of Li was about 0.522 μ m h –1 . The study of Li-coating layer indicates that LIBS technique can be used to assess the degree of re-deposition on the first wall. The variation of H/(H + D) as a function of the days of D-discharge demonstrates that Li-wall conditioning technique can significantly reduce the H/(H + D) ratio in the vacuum vessel due to the strong H/D adsorption capability of Li and enhance long-pulse H-mode plasma operation. The results indicate that LIBS technique can be used for in situ analysis of co-deposition and D retention on the first wall of EAST.